PENDAFTARAN PERALIHAN HAK MILIK ATAS TANAH KARENA JUAL BELI DALAM MEWUJUDKAN TERTIB ADMINISTRASI PERTANAHAN - Suryaningsih, Suryaningsih; Zainuri, Zainuri (Fakultas Hukum Universitas Wiraraja, 2023)
Land is one of the most important factors in human life, everyone needs land for various forms of activities. Based on the provisions of Article 6 paragraph (2) of Government Regulation Number 24 of 1997 that in carrying out land registration, the Head of the Land Office is assisted by the Land Deed Official (PPAT) and other officials determined by statutory regulations. Based on this, this work is to know and understand the implementation of the registration of the transfer of ownership rights to land due to sale and purchase, whether the transfer has realized the orderly administration of land. The implementation of the registration of the transfer of land rights with the status of property rights due to sale and purchase at the Land Office makes the Land Administration Orderly must be implemented in accordance with the regulations governing the transfer of property rights to land due to sale and purchase.